AVALIAÇÃO DA ESTABILIDADE DA FINASTERIDA, ESTUDOS DE COMPATIBILIDADE FÁRMACO-EXCIPIENTES E CONTROLE DE QUALIDADE DAS FORMULAÇÕES FARMACÊUTICAS SÓLIDAS DO MERCADO - Sousa, Igo Pinheiro Lopes e (2020)
Finasteride is a specific competitive inhibitor of the enzyme 5-alfarreductase, an intracellular enzyme responsible for the conversion of testosterone to dihydrotestosterone, used in the treatment of benign prostatic hyperplasia, prostate can